Prevention of acute kidney injury and protection of renal function in the intensive care unit: update 2017: Expert opinion of the Working Group on Prevention, AKI section, European Society of Intensive Care Medicine - Joannidis, M. (Intensive Care Med, 2017)
BACKGROUND: Acute kidney injury (AKI) in the intensive care unit is associated with significant mortality and morbidity. OBJECTIVES: To determine and update previous recommendations for the prevention of AKI, specifically the role of fluids, diuretics, inotropes, vasopressors/vasodilators, hormonal and nutritional interventions, sedatives, statins, remote ischaemic preconditioning and care bundles. METHOD: A systematic search of the literature was performed for studies published between 1966 and March 2017 using these potential protective strategies in adult patients at risk of AKI. The following clinical conditions were considered: major surgery, critical illness, sepsis, shock, exposure to potentially nephrotoxic drugs and radiocontrast. Clinical endpoints included incidence or grade of AKI, the need for renal replacement therapy and mortality. Studies were graded according to the international GRADE system. RESULTS: We formulated 12 recommendations, 13 suggestions and seven best practice statements. The few strong recommendations with high-level evidence are mostly against the intervention in question (starches, low-dose dopamine, statins in cardiac surgery). Strong recommendations with lower-level evidence include controlled fluid resuscitation with crystalloids, avoiding fluid overload, titration of norepinephrine to a target MAP of 65–70 mmHg (unless chronic hypertension) and not using diuretics or levosimendan for kidney protection solely. CONCLUSION: The results of recent randomised controlled trials have allowed the formulation of new recommendations and/or increase the strength of previous recommendations. On the other hand, in many domains the available evidence remains insufficient, resulting from the limited quality of the clinical trials and the poor reporting of kidney outcomes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00134-017-4832-y) contains supplementary material, which is available to authorized users.